Phenotypic variability in west indian cherry genotypes - Gomes, José Everaldo; Perecin, Dilermando; Martins, Antonio Baldo Geraldo; Almeida, Eduardo José de (Pesquisa Agropecuaria Brasileira, 2000)
The measures in the phenotypic variability, correlation, direct and indirect effects in the West Indian cherry (Malpighia emarginata DC.), from Itápolis, São Paulo State, Brazil, aimed to subsidize the management of the selective process in the genotypes. The parameters length and width of leaves, height of plant, diameter of canopy, weight medium of fruit, weight of pulp/fruit, weight medium of 20 fruits and weight medium of pulp of 20 fruits, showed differences for genotypes and date of evaluation. The differences of acidity, size and width medium of fruit are exclusive for dates, suggesting actions of climatic conditions. The height is a good parameter leading to the differentiation for selection of genotypes. The meteorological conditions can influence remarkably the acidity and dimensions of the fruit. Positive associations among leaf length and the parameters that define size and weight of fruits and negative correlation of these parameters with vitamin C were observed; so as positive correlation of size and width of fruits. Brix and canopy diameter were positively correlated with vitamin C. Measures of the leaves are associated positively with size and weight of the fruits and negatively with vitamin C in the studied conditions. The measures of the fruits are directly associated with the characters of weight and yield, that are inversely associated with vitamin C. The selection on Brix can manage the gain in pulp and vitamin C.